Evaluation of Corrosion Resistance of Corrosion Inhibitors for Concrete Structures by Electrochemical Testing in Saturated Ca(OH)2 Solutions with NaCl and Na2SO4. (15th April 2019) - Ryu, Hwa Sung; Lim, Chang Gil; Kang, Tae Won; Lim, Seungmin; Kim, Hong Tae; Shin, Sang Heon
Abstract : Reinforcing steel maintains passivity in an alkaline concrete environment. However, the passive film on the steel can be destroyed as the concrete becomes acidic, which could induce the corrosion of reinforcing steel. Carbonates and sulfates destroy the concrete matrix and accelerate the penetration of hazardous ions, thereby deteriorating the structure. To alleviate the corrosion of internal reinforcing steel within concrete, corrosion inhibitors are most widely used. In this study, the effects of inorganic nitrite (lithium nitrite) and amino acid corrosion inhibitors (diethanolamine, methyl diethanolamine, and 4-aminobutyric) on corrosion resistance and the pH of the solution with various concentrations of Na2 SO4 (0.89, 1.77 g/L) in saturated Ca(OH)2 that contained NaCl (0.98 g/L), which simulated the concrete environment, were investigated. The corrosion resistance of inhibitors was evaluated by corrosion potential, electrochemical impedance spectroscopy, and potentiodynamic techniques. The results indicated improvement of corrosion resistance by the addition of amino acid corrosion inhibitors. It was confirmed that the inhibitor adsorbed on the surface of the specimen and passivated to reduce the corrosion reaction. In addition, the 4-aminobutyric acid corrosion inhibitors had the corrosion protection efficiency of 67.87–77.80%, which is a higher value than that of the inorganic nitrite corrosion inhibitor (lithium nitrite: 69.36–75.93%) and other amino acid corrosion inhibitors (diethanolamine: 35.69–39.91%; methyl diethanolamine: 66.07–69.09%).